Therapeutic Use of Transcranial Direct Current Stimulation in the Rehabilitation of Prolonged Disorders of Consciousness - Aloi, Davide; della Rocchetta, Antonio Incisa; Ditchfield, Alice; Coulborn, Sean; Fernández-Espejo, Davinia (Frontiers in Neurology, 2021)
Patients with Prolonged Disorders of Consciousness (PDOC) have catastrophic disabilities and very complex needs for care. Therapeutic options are very limited, and patients often show little functional improvement over time. Neuroimaging studies have demonstrated that a significant number of PDOC patients retain a high level of cognitive functioning, and in some cases even awareness, and are simply unable to show this with their external behavior - a condition known as cognitive-motor dissociation (CMD). Despite vast implications for diagnosis, the discovery of covert cognition in PDOC patients is not typically associated with a more favorable prognosis, and the majority of patients will remain in a permanent state of low responsiveness. Recently, transcranial direct current stimulation (tDCS) has attracted attention as a potential therapeutic tool in PDOC. Research to date suggests that tDCS can lead to clinical improvements in patients with a minimally conscious state (MCS), especially when administered over multiple sessions. While promising, the outcomes of these studies have been highly inconsistent, partially due to small sample sizes, heterogeneous methodologies (in terms of both tDCS parameters and outcome measures), and limitations related to electrode placement and heterogeneity of brain damage inherent to PDOC. In addition, we argue that neuroimaging and electrophysiological assessments may serve as more sensitive biomarkers to identify changes after tDCS that are not yet apparent behaviorally. Finally, given the evidence that concurrent brain stimulation and physical therapy can enhance motor rehabilitation, we argue that future studies should focus on the integration of tDCS with conventional rehabilitation programmes from the subacute phase of care onwards, to ascertain whether any synergies exist.